Personal Education through Islamic Religious Education in the Generation Zet - Salahudin, Salahudin (Yayasan Insan Mulia Bima, 2024)
The continuous advancement of technology urges individuals to enhance their intellectual and moral maturity. Education plays a crucial role in shaping a generation that is intelligent and morally upright. Islamic religious education serves as the primary foundation, guiding the pursuit of truth, and becomes an essential need for Indonesian society. This research aims to explore character formation through Islamic religious education in the era of Generation Zet. The research method employed is qualitative, focusing on the analysis of literature sources such as books, research journals, and seminar proceedings. From the literature review, it is evident that character education through Islamic religious education is rooted in religious values, Pancasila, culture, and the goals of national education. The implementation of moral values (character) in Islamic Religious Education is carried out through teaching methods, exemplary models, habits, discipline, and consequences to shape students' characters